2021
DOI: 10.1097/corr.0000000000001750
|View full text |Cite
|
Sign up to set email alerts
|

Which Risk Factors Are Associated with Pain and Patient-reported Function in Patients with a Rotator Cuff Tear?

Abstract: Background Patient-reported measures guide physicians in clinical decision making and therefore it is critical to determine what clinical factors are associated with these scores. Psychological and physical factors are commonly studied separately in patients with rotator cuff tears to determine their influence on outcomes. It is well established that psychological distress and scapular motion change in the presence of a symptomatic rotator cuff tear. However, these factors have not been studied sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Pain-free function acquisition is one of the important factors in patients with RC tears. 44 In the present study, a statistically significant reduction in pain was found in both groups similar to the literature, whereas none of the groups were superior to the other. 45,46 Patient satisfaction is an important parameter that evaluates the success of the treatment from the patient's perspective.…”
Section: Discussionsupporting
confidence: 90%
“…Pain-free function acquisition is one of the important factors in patients with RC tears. 44 In the present study, a statistically significant reduction in pain was found in both groups similar to the literature, whereas none of the groups were superior to the other. 45,46 Patient satisfaction is an important parameter that evaluates the success of the treatment from the patient's perspective.…”
Section: Discussionsupporting
confidence: 90%
“…Scapular dysfunction is common in patients with chronic shoulder pain and rotator cuff disease [4]. This study confirmed that scapular motion was associated with patient-reported shoulder pain and function [5]. But, again, further study is needed to determine which treatment strategies work to help improve this part of the problem.…”
Section: Where Do We Need To Go?mentioning
confidence: 62%
“…In the current study, Lemaster et al [5] investigated the psychological and physical factors, as well as shoulder function by American Shoulder and Elbow Surgeons (ASES) score, in patients with rotator cuff tears. They found that patient factors (including age), physical factors (like scapular motion), and psychological factors (fear-avoidance beliefs or acceptance of chronic pain, for example) all were associated with ASES score.…”
Section: What Are We Now?mentioning
confidence: 99%
“…We similarly found no relationship between OSPRO-YF score and the NRS pain score. This finding was surprising, as prior research has demonstrated that the constructs measured in the OSPRO-YF are associated with postoperative pain intensity 23,32,33,48 as well as perceived physical function. 2,20,23,41,48 Postoperative pain is a complex phenomenon with myriad contributing factors.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 82%
“…This finding was surprising, as prior research has demonstrated that the constructs measured in the OSPRO-YF are associated with postoperative pain intensity 23,32,33,48 as well as perceived physical function. 2,20,23,41,48 Postoperative pain is a complex phenomenon with myriad contributing factors. The mean postoperative NRS pain score was low (1.4 of 10), and 58.9% of patients reported no pain.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 82%